Quality of seedlings of Parapiptadenia rigida (Benth.) Brenan produced in different substrates with sewage sludge and rice hulls - Santos, Fernando Elair Vieira; Caldeira, Marcos Vinicius Winckler; Kunz, Sustanis Horn (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
The substrate has a significant influence on seedling development, and there are several materials that can be used in its composition. The aim of this study was to evaluate the quality of seedlings of Parapiptadenia rigida (Benth.) Brenan produced on different substrates sewage sludge compost and rice hulls and rice husk in natura. The work was carried out at the nursery of the Center of Agricultural Sciences (CCA) UFES in the municipality of Alegre-ES in the period from november to march. The experimental design was completely randomized, consisting of nine treatments with five replicates of four plants. The substrates were formulated with different ratios of sewage sludge (LE) (80, 60, 40 and 20%) associated with rice hulls (CAC) and rice husk in nature (CAN) and a control consisting of 100% commercial substrate base pine bark. In general, there was beneficial effect on the development of the species by the addition of rice hulls and rice husk in nature. However using the commercial substrate had a negative effect on their growth. Treatment T7 (40% CO:60% CAN) was the best, with the highest average of the characteristics of growth.